Does aid for trade promote import diversification? - Ly-My, Dung (2022)
Many studies have found that Aid for Trade (AfT) is effective in promoting the exports and imports of recipient countries. Recently, Gnangnon (The World Economy, 42, 2019 and 396) and Kim (The World Economy, 42, 2019 and 2684) found that AfT also contributes to the export diversification of recipient countries. We extend previous studies by assessing the effects of AfT on import diversification of recipient countries by estimating a two-step System GMM on a data set of 104 countries in 2003–2016. Our empirical results reveal that AfT contributes to the diversification of both import commodities and import partners. This effect is particularly strong when partner countries are Non-DAC countries. Our empirical evidence further strengthens the case for AfT because previous literature indicates that both export and import diversification are beneficial.